High-Fat Diet-Related Obesity Promotes Urethane-Induced Lung Tumorigenesis in C57BL/6J Mice - Shi, Dan; Wu, Jingjing; Wu, Youqile; Lin, Xiaojing; Xu, Cai; Lian, Xuemei (Frontiers in Oncology, 2021)
Epidemiological studies have recently shown that obesity increases lung cancer risk, but the underlying biological connection is unclear. To determine whether high-fat diet (HFD)-induced obesity influences the susceptibility to chemical-induced lung tumorigenesis, a HFD feeding condition was combined with a multi-dose urethane-induced lung tumorigenesis model using C57BL/6J mice. In cell culture models, lung cancer cell lines A549 and H460 were used to investigate the effect of leptin on cell viability and its underlying mechanism of action. The results showed that obesity was induced with a 60 kcal% HFD feeding. Serum leptin levels increased with HFD feeding and further increased in urethane-administered and HFD-fed mice. Compared to the control diet-fed mice, the HFD-fed mice exhibited increased lung tumor burden and typical pro-tumorigenic STAT3 pathway activation in lung tissues after urethane administration. In vitro, leptin significantly increased the viability of lung cancer cell lines A549 and H460 in a dose-dependent manner by activation of STAT3, Bcl-2, and cyclin D1. These effects were significantly attenuated when PI3K or mTOR were inhibited by LY294002 or rapamycin, respectively. These results suggested that HFD-induced obesity could promote the development of lung tumorigenesis in C57BL/6J mice, and leptin-mediated activation of the PI3K/Akt/mTOR/STAT3 pathway was probably involved in this mechanism.